Does stock market take into consideration football players’ injuries? - Mrhari, El Mehdi; Hasssouni, Mohammed (Research Papers in Economics and Finance, 2023)
Injuries are a frequent risk in sports. This article analyses the repercussions of football players’ injuries on the market returns of six European clubs: Ajax, Borussia Dortmund, Manchester United, Olympique Lyonnais, Benfica and Juventus over a period of three years. The originality of this study comes from the absence of scientific articles in this field. Based on the event study methodology, the results indicate that the sensitivity of stock prices to injuries is very low. Furthermore, the results show that the date of injury is a significant variable causing the effect on returns (Borussia Dortmund). However, injury severity, player status and COVID do not influence the price share.